If it's not what You are looking for type in the equation solver your own equation and let us solve it.
n in (-oo:+oo)
((-7*n)/12)*((9*n)/14) = 0
-3/8*n^2 = 0 // : -3/8
n^2 = 0
n = 0
n = 0
| 9-5x=6x | | (2y-3)/(y+3)=5/7 | | 2h+5=3 | | 5x+3=10x+-7 | | 123+75=180 | | (-55)-(-88)= | | 6(7+x)+5x=0 | | -(8-4h)= | | 6f-1=2 | | 4s^4-17s^2+4=0 | | 176+4= | | 5x=7y+28 | | 9+5a=2a+5 | | 2x-1/3x=15 | | (3/8)(8/3)(n) | | (5/16)+(2/3)x=(1/4)-(1/6)x | | (-72)+36= | | (3/8)(8/3) | | A/4+7=22 | | 1-1/2-1/3 | | 2(0.6x+x)= | | (3k-3)(7k+7)= | | -8=p-5 | | -10b+2b+b=0 | | 5x+17x-8=180 | | 2(1.2)= | | (-76)+(-84)= | | (3x-6)(3x-6)=0 | | 27-9x=4x+8 | | 4(x+9)+5x= | | 2x-5=?(x+4) | | (-15)+(-7)= |